DNA Extraction and Amplification of ITS2 Maker for Authentication of Tongkat Ali Herbal Product - Nurul Atiqah Othman 1993- 637493; Alina Wagiran supervisor 465169; Fakulti Biosains dan Biokejuruteraan 559340 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2016)
Project Paper (Sarjana Muda Sains (Biologi Industri)) - Universiti Teknologi Malaysia, 2016